(untitled) (Altre Modernità, 2019)
Migration is a complex phenomenon with multiple edges. It brings together macro economic, social and political processes, as well as the micro level of the intimate experiences of families and individuals. This text offers a proposal to study one of the aspects that has been left aside from migration studies: the affective dimension of the people affected by migration; in this specific case, by women who have migrated or who are wives, mothers, sisters or daughters of migrants. The use of an ethnographic methodology and the use of resources such as interview-stories make it possible to approach –through language– the emotions that migration triggers, such as uncertainty, sadness, shame, pain, among others. The analysis of the stories leads us to propose a series of reflections about how migration is experienced in the emotional field and how the affective dimension is a fundamental part of decision-making and, therefore, in the transformations of the dynamics in the family groups and in the community.